Politics of Corruption in Albanian Higher Education - Shahini, Arjan; Zhllima, Edvin; Imami, Drini (Studies of Transition States and Societies, 2024)
This paper examines the persistent issue of corruption in Albania, which continues to plague crucial areas of higher education such as learning assessment. Emphasising the significant impact of political influence on student evaluations, the article draws on survey results to address the issue. It suggests that this influence stems from historical factors and current political dynamics. In addition, the paper analyzes the exploitation of anti-corruption rhetoric in higher education as a tool for political control, and discusses the considerable challenges which anti-corruption campaigns face due to political interference and institutional resistance. In conclusion, the paper argues that a holistic approach, considering historical, institutional, and political contexts, is essential for effectively observing corruption in higher education.